Permanent, seasonal, and episodic seismic sources around Vatnajökull, Iceland from the analysis of correlograms - Nowé, Sylvain; Lecocq, Thomas; Caudron , Corentin; Jónsdóttir, Kristín; Pattyn , Frank (Volcanica, 2021)
In this study, we locate and characterise the main seismic noise sources in the region of the Vatnajökull icecap (Iceland). Vatnajökull is the largest Icelandic icecap, covering several active volcanoes. The seismic context is very complex, with glacial and volcanic events occurring simultaneously and the classification between the two can become cumbersome. Using seismic interferometry on continuous seismic data (2011–2019), we calculate the propagation velocities and locate the main seismic sources by using hyperbolicas geometry and a grid-search method. We identify and characterise permanent oceanic sources, seasonal glacial-related sources, and episodic volcanic sources. These results give a better understanding of the background seismic noise sources in this region and could allow the identification of seismic sources associated with potentially threatening events in real-time.